Pengaruh kualitas sistem, kualitas informasi, dan kualitas layanan terhadap kepuasan pengguna e–learning di Perguruan Tinggi - Satyadarma, Muhammad Fakhrurrozi; Syamsudin, Syamsudin (Bulletin of Educational Management and Innovation, 2023)
E-learning as a learning system is expected to improve the quality of student learning. Satisfaction of using the system is influenced by the quality of the system, the quality of information and the quality of service. This study aims to test and obtain empirical evidence on the effect of system quality, information quality, and service quality on user satisfaction of e-learning system in learning at Islamic Education Study Program of Universitas Muhammadiyah Yogyakarta This type of research was quantitative research with survey method. The population in this study was Islamic Education students of Universitas Muhammadiyah Yogyakarta Batch of 2017, 2018, and 2019, with a sample of 252 respondents. Data collection method used proportional random sampling with questionnaire instrument. Data analysis used regression analysis with the help of IBM SPSS Statistic ver. 26 software. The results of this study showed that System Quality had a significant positive effect on User Satisfaction. Information Quality had a significant positive effect on User Satisfaction. The Service Quality had a significant positive effect on User Satisfaction.